Induced expression of NOX and SOD by gaseous sulfur dioxide and chlorine dioxide enhances antioxidant capacity and maintains fruit quality of ‘Daw’ longan fruit during storage through H2O2 signaling - Atinut Joradol (2019)
© 2019 Elsevier B.V. Hydrogen peroxide (H2O2) is known to be a signaling molecule involved in the activation of plant defense against both biotic and abiotic stresses. The current study aimed to demonstrate that fumigation induces H2O2 production, which is believed to act as the upstream signaling molecule in the antioxidant defense responses. Longan (Dimocarpus longan Lour. cv. Daw) fruit were fumigated with either 1000 mg L−1 sulfur dioxide (SO2) or 10 mg L−1 chlorine dioxide (ClO2), or in combination, and stored for 8 d. Both types of fumigation reduced pericarp browning and maintained fruit quality for up to 3, 5 or 7 d, respectively, comparing with a 2 d shelf life for the non-fumigated control fruit. 2,2’-Azino-bis-3-ethylbenzthiazoline-6-sulphonic acid (ABTS) and 1,1-diphenyl-2-picrylhydrazy (DPPH) assays indicated that antioxidant capacity was enhanced in treated fruit. H2O2 concentrations increased immediately after the fumigation in treated fruit, reaching a maximum within 6–12 h. Treatments increased expression of the plasma membrane nicotinamide adenine dinucleotide phosphate oxidase (RbohD) and superoxide dismutase (SOD). Subsequent nicotinamide adenine dinucleotide phosphate oxidase (NOX) and superoxide dismutase activity surges coincided with the rise of H2O2. Compared with the fumigated samples, H2O2 concentrations did not increase in the control until day 1, reaching concentrations that were about three times higher than those of the fumigated samples at the end of the experiment, while that of the fumigated fruit remained lower. These results suggested that SO2 and/or ClO2 fumigation triggers the NOX-dependent H2O2 generation, which could activate the antioxidant response in longan aimed to overcome the subsequent H2O2 production, thereby reducing the pericarp browning and maintaining fruit quality.